Extract of Ziziphus jujuba Fruit (Jujube) Stimulates Expression of Enzymes Responsible for Heme Recycle via Anti‐oxidant Response Element in Cultured Murine Macrophages. (8th December 2015) - Chen, Jianping; Lam, Candy T. W.; Li, Zhonggui; Yao, Ping; Lin, Huangquan; Dong, Tina T. X.; Tsim, Karl W. K.
Abstract : Jujube, the fruit of Ziziphus jujuba Mill., is a functional food and commonly used as a health supplement worldwide. To study the beneficial role of jujube in heme iron recycling during erythrophagocytosis, the expression of heme oxygenase‐1 (HO‐1), biliverdin reductase A and B, and ferroportin were determined in jujube‐treated cultured RAW 264.7 macrophages. Application of a chemically standardized jujube water extract in cultured RAW 264.7 cells for 24 h stimulated the expressions of HO‐1, biliverdin reductase A, biliverdin reductase B, and ferroportin in a concentration‐dependent manner, having the maximal responses from twofolds to threefolds. A plasmid containing anti‐oxidant response element, a regulator for HO‐1 transcription, was transfected into RAW 264.7 cells. Application of jujube water extract onto the transfected macrophages stimulated the anti‐oxidant response element‐mediated transcriptional activity by twofolds. These results supported the potential capacity of jujube by regulating expressions of heme iron recycling genes in cultured macrophages. Copyright © 2015 John Wiley & Sons, Ltd.